Direct Method to Determine the Antibiotic Susceptibility of Rapidly Growing Blood Pathogens - Wegner, Dennis L. (1976)
Standardized direct disk diffusion antibiotic susceptibility testing on monomicrobial blood cultures is compared with the Food and Drug Administration method. The direct method yields acceptable data and may conserve 24 h in reporting results.